Quercetin protects cardiomyoblasts against hypertonic cytotoxicity by abolishing intracellular Ca2+ elevations and mitochondrial depolarisation - Dostál, Z; Zholobenko, A V; Přichystalová, H; Gottschalk, B; Valentová, K; Malli, R; Modrianský, M (Biochemical pharmacology, 2024)
BACKGROUND AND AIM: Osmotic changes represent a burden for the body and their limitation would be beneficial. We hypothesized that ubiquitous natural compounds could guard against cytotoxic effects of osmotic stress. We evaluated the anti-hypertonic mechanism of quercetin and 2,3-dehydrosilybin in H9c2 cells in vitro. EXPERIMENTAL PROCEDURE: Protective effect of both compounds was determined by neutral red assay, cell apoptosis was estimated by measuring caspase-3 activity and verified by western blot and annexin V assay. Phosphorylation level of selected proteins was also detected. Mitochondrial membrane potential was evaluated using dye JC-1. Ca2+ signals were evaluated using genetically encoded fluorescent Ca2+ biosensor GCaMP7f. Formation of reactive oxygen species was measured using an oxidant-sensing probe dihydrofluorescein diacetate. KEY RESULTS: Quercetin protected H9c2 cells against hypertonic stress-induced cell death. We observed a significant increase in intracellular Ca2+ levels ([Ca2+]cyto) when cells originally placed in a hypertonic solution were returned to a normotonic environment. Quercetin was found to prevent this increase in [Ca2+]cyto and also the depolarization of mitochondrial membrane potential. CONCLUSIONS AND IMPLICATIONS: Quercetin, but not 2,3-dehydrosilybin, reduced adverse effects of osmotic stress mainly by dampening the elevation of [Ca2+]cyto and mitochondrial Ca2+ overload. This may consequently prevent MPTP pore opening and activation of apoptosis.
Keywords: reaktivní formy kyslíku; buněčná smrt; Oxidative Stress; Hypertonic stress; mitochondrie; apoptóza; quercetin; Quercetin; Calcium; oxidační stres; Reactive Oxygen Species; membránový potenciál mitochondrií; Mitochondria; Cell Death; Membrane Potential, Mitochondrial; 2,3-dehydrosilybin; H9c2 cells; Apoptosis